2020
DOI: 10.2217/fon-2020-0937
|View full text |Cite
|
Sign up to set email alerts
|

The LEAP Program: Lenvatinib Plus Pembrolizumab for the Treatment of Advanced Solid Tumors

Abstract: Tumor progression and immune evasion result from multiple oncogenic and immunosuppressive signals within the tumor microenvironment. The combined blockade of VEGF and inhibitory immune checkpoint signaling has been shown to enhance immune activation and tumor destruction in preclinical models. The LEAP clinical trial program is evaluating the safety and efficacy of lenvatinib (a multikinase inhibitor) plus pembrolizumab (a PD-1 inhibitor) across several solid tumor types. Preliminary results from ongoing trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 29 publications
0
34
0
1
Order By: Relevance
“…This suggests a profound effect of lenvatinib on the microenvironment leading to increased pembrolizumab activity. In the gastric/esophageal arm of the LEAP study, the combination showed more modest benefits with a response rate of 39% and PFS of 7.4 months [35]. This combination will be tested further in the future.…”
Section: Combination With Lenvatinibmentioning
confidence: 96%
“…This suggests a profound effect of lenvatinib on the microenvironment leading to increased pembrolizumab activity. In the gastric/esophageal arm of the LEAP study, the combination showed more modest benefits with a response rate of 39% and PFS of 7.4 months [35]. This combination will be tested further in the future.…”
Section: Combination With Lenvatinibmentioning
confidence: 96%
“…When local disease control is needed for advanced disease, TACE may be indicated for use alone or in combination with systemic therapy. A current phase III study is evaluating TACE in combination with Lenvatinib and Pembrolizumab for advanced, non-metastatic disease[ 37 ]. In addition to being useful in stratifying patients to appropriate treatment, BCLC class is a useful tool in prognosticating survival following TACE, with many studies stratifying survival based on these categories.…”
Section: Tacementioning
confidence: 99%
“…Further studies are therefore needed to elucidate the role of FGFRs in modulating tumor immune response. Interestingly, combination of FGFR inhibitors and immunotherapy showed promising therapeutic effect in multiple solid tumors in clinical trials [137][138][139], and the underlying mechanisms of action still need to be fully understood.…”
Section: Fibroblast Growth Factor Receptorsmentioning
confidence: 99%
“…Figure 3 shows the role of other oncogenes to regulate PD-L1 expression in cancer cells including c-Myc, p53, EML4-ALK, K-ras and EGFR. tion of FGFR inhibitors and immunotherapy showed promising therapeutic effect in multiple solid tumors in clinical trials [137][138][139], and the underlying mechanisms of action still need to be fully understood.…”
Section: Epidermal Growth Factor Receptormentioning
confidence: 99%